RE-SHARAH OF HADITH AS A NEW ISLAMIC SCIENCE: AN APPLICATION OF THOMAS KUHN’S SCIENTIFIC REVOLUTION PARADIGM - Rukmana, Fachruli Isra; Hidayat, M. Riyan; Yuzar, Sri Kurniati (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2023)
This article discusses the use of Thomas Kuhn's paradigm of the scientific revolution in presenting the discourse of re-syarah hadith which has been less objective in addressing the social problems of the people. The description of Kuhn's framework of thought on the revitalization of the hadith scribe is quite extensive, including the stages in providing an overview to give birth to a breakthrough in the science of hadith from the time of the companions to the rapid development of hadith in the 2nd to 3rd centuries. By starting from the questions, first, what is the framework of Thomas Kuhn's scientific revolution, second, what are the basic assumptions of the need for rewriting hadith in the current era, third, how is the application of Thomas Kuhn's scientific revolution paradigm in the discourse of rewriting hadith. The type of research used in this analysis is idea analysis with a library research approach. Typically, this research centers on two data models, namely primary data and secondary data. By applying the study of the interpretation of thought, this article can show that Thomas Kuhn's scientific revolution paradigm is a good reference in discussing the re-syarah of hadith in the present era, in addition to the discourses of re-writing hadith, this is the basis in showing that Islam through the Prophet's hadith has strong integrity to discuss the issue of contextual re-writing of hadith, because in its history Islam is full of knowledge, not only in terms of religion but also in terms of social life.[Artikel ini berbicara penggunaan paradigma revolusi ilmiah Thomas Kuhn dalam menyuguhkan wacana re-syarah hadis yang saat ini kegunaannya mulai tidak begitu objektif untuk menjawab persoalan sosial umat. Penggambaran kerangka berpikir Kuhn mengenai revitalisasi syarah hadis cukup ekstensif, termasuk tahapan-tahapannya dalam memberikan gambaran untuk melahirkan dobrakan baru terhadap science hadis dari mulai masa sahabat sampai perkembangan hadis yang pesat di abad-2 sampai 3 H. Dengan beranjak dari persoalan, pertama, bagaimana kerangka pemikiran Thomas Kuhn terhadap revolusi ilmiah, kedua, apa asumsi dasar perlunya re-syarah hadis pada era saat ini, ketiga, bagaimana pengaplikasian paradigma revolusi ilmiah Thomas Kuhn dalam wacana re-syarah hadis. Jenis penelitian yang digunakan dalam analisis ini merupakan analisis gagasan dengan pendekatan kepustakaan (library research). Secara distingtif, penelitian ini berpusat pada dua model data yakni data primer dan data sekunder. Dengan menerapkan kajian interpretasi pemikiran, artikel ini mampu menunjukkan bahwa paradigma revolusi ilmiah Thomas Kuhn merupakan acuan yang besar dalam mendiskusikan re-syarah hadis di era saat ini, di samping itu memang terdapat wacana-wacana penggagasan ulang terhadap syarah hadis, ini menjadi landasan dalam menunjukkan bahwa agama Islam melalui hadis Nabi mempunyai integritas yang kuat untuk berdiskusi persoalan perombakan syarah hadis kontesktual karena dalam historinya Islam penuh dengan ilmu pengetahuan, tidak hanya dari kacamata keagamaan, namun juga dari bagian sosial kehidupan.]